KETAATAN HUKUM MASYARAKAT MAKASSAR DALAM PENERAPAN PROTOKOL KESEHATAN COVID-19 - Sagita J, Mutiara; Paserangi, Hasbir; Heryani, Wiwie (Universitas Ekasakti, 2023)
The Makassar City Government has carried out government functions by demonstrating the realization of measurable programs and regulations in handling the Covid-19 pandemic in Makassar City. Several strategic steps have become examples for other local governments, such as procuring isolation places on ships in collaboration with PT—Indonesian National Shipping (Pelni) for Covid patients in the mild category. The level of legal compliance of the people in Makassar City in implementing health protocols as an Effort to Prevent and Control Corona Virus Disease in 2019, the majority are at the Compliance level (fulfillment of wishes) due to fear of being penalized. At the identification level, namely, compliance to maintain good relations with enforcement officials law enforcement, some of them have law enforcement relatives, and very few are at the level of internalization who comply with the rules because they know the purpose of the regulations for implementing health protocols and know the dangers of transmitting the Covid-19 virus. Factors that become obstacles in implementing health protocols in handling the Covid-19 pandemic are a) Community saturation factor. b) The inconvenience factor of using a mask. c) The factor of public knowledge of the dangers of Covid-19 is limited